Results of iliac crest biopsies taken from 1465 patients with primary breast cancer - Solomayer, Erich-Franz; Diel, Ingo J.; Krempien, Burkhard; Meyberg-Solomayer, Gabriele Christine; Gollan, Christina; Krainick-Strobel, Ute Elisabeth; Wallwiener, Diethelm; Bastert, Gunther (Journal of cancer research and clinical oncology, 1998)
This study was performed to analyze the relevance of iliac crest biopsy in patients with primary breast cancer with regard to metastases of the primary tumor and osteogenic disease. We performed intraoperative bilateral biopsy of the anterior iliac crests in 1465 patients with primary breast cancer. The bone specimens were histologically evaluated with regard to quality of the biopsy, tumor involvement, and osteogenic and hematogenic disease. Accurate and clear evaluation of the iliac crest biopsies was possible in 1365 patients (93%). Osteopenia was diagnosed in 48 patients (3.5%); 24 patients (1.7%) showed histological evidence of tumor involvement of the skeletal system. All these 24 patients received systemic (adjuvant) therapy after surgery. Ten patients had micrometastases, although in 5 of them both the postoperative bone scan and X-rays showed no pathological results. In 10 women with histologically negative bone biopsies, metastases to the bone were diagnosed by bone scan and radiological methods. Random perioperative iliac bone biopsy cannot be recommended in patients with primary breast cancer. Iliac crest biopsy is relevant in certain scenarios (e.g. suspected recurrence, doubtful bone scan).
Gesehen am 14.03.2024